Relationship of brand image, in-flight service quality and passengers' satisfaction on repurchase intention - Yen Yen, Yow (2019)
Repurchase intention is vitals in airline industry. A highly intense market demanded airline’s operators to remain competitive by maintaining customer satisfaction. This is because satisfied passengers have a higher propensity to repurchase the same brand. Based on the literature, brand image and in-flight service quality could affect passengers’ satisfaction and subsequently repurchase intention. Therefore, this study attempts to examine the relationship between brand image, in-flight service quality and repurchase intention. Besides, this study also examines the mediating effect of passengers’ satisfaction on the relationship between brand image, in-flight service quality and repurchase intention. For the purpose of the study, quantitative research method through survey questionnaire was employed to examine the proposed relationship. A total of 800 questionnaires were distributed in the Kuala Lumpur International Airport, Kuala Lumpur International Airport 2, and Penang International Airport. A total of 299 responses were received, representing a 37.38% response rate. The data was analysed using SmartPLS 3.0 and reveal that all the hypotheses were supported. The findings reveal that brand image and in-flight service quality positively influence repurchase intention. The findings further reveal that passengers’ satisfaction positively influences repurchase intention. The findings also shown that there is a significant mediating effect of passengers’ satisfaction on the relationship between brand image and in-flight service quality and repurchase intention. Limitations and recommendations for future study are also provided.